Social marketing: advancing a new planning framework to guide programmes. (31st May 2021) - Akbar, M. Bilal; Ndupu, Lawrence B.; French, Jeff; Lawson, Alison
Abstract : Purpose: This paper aims to develop and present a new planning framework of social marketing, known as consumer research, segmentation, design of the social programme, implementation, evaluation and sustainability (CSD-IES). Design/methodology/approach: The proposed framework is based on recent theoretical developments in social marketing and is informed by the key strengths of existing social marketing planning approaches. Findings: The CSD-IES planning framework incorporates emerging principles of social marketing. For example, sustainability in changed behaviour, ethical considerations in designing social marketing programmes, the need for continuous research to understand the changing needs of the priority audience during the programme and the need for explicit feedback mechanisms. Research limitations/implications: The CSD-IES framework is a dynamic and flexible framework that guides social marketers, other practitioners and researchers to develop, implement and evaluate effective and sustainable social marketing programmes to influence or change specific behaviours based on available resources. Originality/value: This paper makes an important contribution to social marketing theory and practice by integrating elements of behaviour maintenance, consideration of ethical perspectives and continuous feedback mechanisms in developing the CSD-IES framework, bringing it in line with the global consensus definition of social marketing.